Spacing between graphene and metal substrates studied with total-reflection high-energy positron diffraction. (July 2016) - Fukaya, Yuki; Entani, Shiro; Sakai, Seiji; Mochizuki, Izumi; Wada, Ken; Hyodo, Toshio; Shamoto, Shin-ichi
Abstract: The spacing between graphene and metal substrates has been investigated using total-reflection high-energy positron diffraction (TRHEPD). The rocking curve analysis performed, based on the dynamical diffraction theory, shows that the spacing between the graphene layer and a substrate of Cu(111) and that between graphene and a Co(0001) substrate are 3.34 Å and 2.06 Å, respectively. The former is close to the interlayer spacing in graphite, suggesting a weak interaction with the substrate material, whereas the latter value experimentally verifies that, in the case of graphene on Co(0001), there is a strong interaction with the substrate.